The Effectiveness of Conflict Management in Overcoming Problems at Bank BJB Syariah Cirebon Branch - Apriliani, Andhini; Salam, Abdus; Haerisma, Alvien Septian (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2024)
Internal conflict within financial institutions, including Islamic banks, has become a major concern in organizational management literature. One of the main challenges often faced by banks, including Bank BJB Syariah Cirebon Branch, is internal conflict. This research aims to answer questions from the problem formulation, namely to find out how internal conflicts arise and influence performance, implementation of conflict management, and the effectiveness of conflict management in resolving problems at Bank BJB Syariah Cirebon Branch. The research method used is a qualitative descriptive method, the data sources used are primary and secondary data sources with data collection techniques through interviews, literature study and documentation. The research results show that the factors causing conflict at Bank BJB Syariah Cirebon Branch are different goals regarding the distribution of financing, communication errors, and differences of opinion. The implementation of conflict management at Bank BJB Syariah Cirebon Branch is carried out using five methods, namely competition, collaboration, avoidance, compromise and accommodation. Bank BJB Syariah Cirebon Branch has succeeded in implementing effective conflict management, which not only produces an agreement that is acceptable to all parties, but also carries out the conflict resolution process well. This success not only creates a harmonious environment among stakeholders, but can also have a positive impact on the image and reputation of Bank BJB Syariah Cirebon Branch.